2005
DOI: 10.1111/j.1439-0418.2005.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

(11Z)‐hexadec‐11‐enal enhances the attractiveness of Diatraea saccharalis main pheromone component in wind tunnel experiments

Abstract: GC-EAD and GC-MS analysis of pheromone gland extracts of sugarcane borer, Diatraea saccharalis, revealed two antennally active compounds, (9Z,11E)-hexadeca-9,1-dienal and (11Z)-hexadec-11-enal, in approximately 10 : 1 ratio. Various doses of identified compounds were investigated in wind tunnel experiments individually and in a 10 : 1 ratio. At all tested doses (9Z,11E)-hexadeca-9,1-dienal alone elicited upwind orientation and source location only in a minority of tested males. An admixture of (11Z)-hex-11-ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The reproductive isolation between populations may rapidly develop in response to a variety of factors. Such factors may be differences between environments, low dispersal capacity, geographical barriers, insect host plant association, different agricultural production systems, composition of sex pheromones, and different colonization and foundation events (Butlin, ; Rice, ; Burke & Arnold, ; Kalinova et al., ; Bickford et al., ; Cortés et al., ; Joyce et al., ; Pavinato et al., ). Therefore, it is to be expected that a genetic mechanism that could influence the evolution of reproductive isolation does not act in the same way in the various combinations of SCB populations studied.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive isolation between populations may rapidly develop in response to a variety of factors. Such factors may be differences between environments, low dispersal capacity, geographical barriers, insect host plant association, different agricultural production systems, composition of sex pheromones, and different colonization and foundation events (Butlin, ; Rice, ; Burke & Arnold, ; Kalinova et al., ; Bickford et al., ; Cortés et al., ; Joyce et al., ; Pavinato et al., ). Therefore, it is to be expected that a genetic mechanism that could influence the evolution of reproductive isolation does not act in the same way in the various combinations of SCB populations studied.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results are reported in the literature (Cabrera et al 2001, Yang et al 2002, 2007, Kawazu et al 2007, Yu-yong et al 2009. The component (Z,E)-9,11-hexadecadienal is also the major sex pheromone component from the phylogenetically related specie Diatraea saccharalis (Fabricius) (Svatoš et al 2001, Palacio Cortés et al 2010, but the attractiveness of this compound is lower than that of caged virgin females in field experiments (Hammond & Hensley 1971, Perez & Hensley 1973, Batista-Pereira et al 2002, Kalinová et al 2005.…”
Section: Resultsmentioning
confidence: 97%
“…Such an outcome was somewhat unexpected because the sex pheromone of D. saccharalis females has received considerable research attention (Patrick and Hensley 1970;Hammond and Hensley 1971;Perez and Hensley 1973;Svatoš et al 2001;Batista-Pereira et al 2002;Santangelo et al 2002) and has been shown to be highly attractive to D. saccharalis males in laboratory experiments. Indeed, the effect exerted by a two-component pheromone comprising (9Z,11E)-hexadecadienal and (Z)-11-hexadecenal was reportedly comparable with that of D. saccharalis virgin females in laboratory wind tunnel experiments (Kalinová et al 2005).…”
Section: Introductionmentioning
confidence: 82%
“…Z 11–16:Ald has also been found as a minor component in extracts of D. saccharalis females (Batista‐Pereira et al. 2002) where it enhances significantly the attractiveness of the main sex pheromone component (9 Z ,11 E )‐hexadecadienal (Kalinová et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation